A Commitment to Religious Freedom as the Bond that Makes Us Free: Reinvigorating Security, Religious Autonomy, and the Good Society. Issue 4 (2nd October 2022) - Scharffs, Brett G.
Abstract : This article is a continuation of my search for a better metaphor than "balancing" to seek mutual vindication of the important values of security and religious freedom. Here I suggest the metaphor of how resin helps hold together layers of fabric to create fiberglass or Kevlar. The resin, I suggest, that binds the sheets of material together are the basic fundamental values that underly liberal constitutionalism—including the rule of law, due process, the presumption of innocence, and equal protection. I focus particularly on important messages from George Washington to religious communities upon his election as President and his message to his fellow countrymen upon his retirement for guidance about the importance of religious freedom to the democratic experiment in self-government.